Свобода и идеологизация. Русская публицистика 2022 года после вторжения России в Украину - Righi, Lara (Studia Rossica Posnaniensia, 2025)
The article aims at illustrating Russian authors’ main ideological perspectives expressed in 2022 concerning the Russian invasion of Ukraine. Growing waves of patriotism and imperialism in the Russian Federation are at the basis of the aggression. Under the influence of restorative nostalgia, the government perceives itself as the heir of the bygone greatness of the Soviet Union, that must then be re-established. Because of closer and closer political relations between Ukraine and Europe from 2010s on, the Russian government perceives the former as the traitor of the commonly shared Soviet past. Hence, the Soviet dichotomy between us and them is reintroduced to define Russia and Ukraine respectively. This opposition can be used to classify Russian authors on the basis of their opinions regarding the aggression expressed in the journalistic field; those who publicly side with power in Russia are us, while them labels authors who choose either migration or underground culture to oppose the Russian government.